2022
DOI: 10.1016/j.ijpam.2022.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the epidemiology and impact of the COVID-19 pandemic on domestic violence and child abuse in Saudi Arabia

Abstract: Objectives: The purpose of this paper is to highlight the impact of a pandemic on the lives of vulnerable members of the community who have experienced or are 'at risk' of experiencing intimate family violence and child abuse in Saudi Arabia. By reviewing the experience in Saudi Arabia in the context of the international literature, the study explores similarities and differences in the impact of the pandemic on family violence. Methods: The study inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…It can be identified easily from the cases that, in most situations, IPV occurred due to the grief of forced quarantine-based economic insecurity and fear of job loss that was mostly responsible for the reduction in sources of income. We can observe that the findings are more or less consistent with the earlier findings reported by numerous authors such as Alkhattabi et al, 2023;Tripathi et al, 2022;Morgan and Boxall, 2022;Moyer et al, 2022;Miller et al, 2021;Fraser, 2020;Rajah and Osborn, 2020;and Zou, 2020. However, the specific causes and consequences were different in all those cases.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…It can be identified easily from the cases that, in most situations, IPV occurred due to the grief of forced quarantine-based economic insecurity and fear of job loss that was mostly responsible for the reduction in sources of income. We can observe that the findings are more or less consistent with the earlier findings reported by numerous authors such as Alkhattabi et al, 2023;Tripathi et al, 2022;Morgan and Boxall, 2022;Moyer et al, 2022;Miller et al, 2021;Fraser, 2020;Rajah and Osborn, 2020;and Zou, 2020. However, the specific causes and consequences were different in all those cases.…”
Section: Discussionsupporting
confidence: 92%
“…For example, a recent study conducted in Saudi Arabia identified that the risk of family violence and child abuse increased during Covid-19 pandemic in Saudi Arabia, similar to findings in other countries. In contrast, they reported decreased reports/complaints due to factors associated with Covid-19 outbreak (Alkhattabi et al , 2023).…”
Section: Background and Introductionmentioning
confidence: 96%
See 3 more Smart Citations